Metatheories and Metaphors of Organizational Identity: Integrating Social Constructionist, Social Identity, and Social Actor Perspectives within a Social Interactionist Model. (July 2017) - Haslam, S. Alexander; Cornelissen, Joep P.; Werner, Mirjam D.
Abstract: This review examines three dominant metatheories of organizational identity that are grounded in social constructionist, social identity, and social actor theorizing. It focuses on root metaphors of framing, categorization and personification that are associated with each metatheory and outlines differences in their assumptions, key constructs, and forms of analysis. The review shows how the emphasis of each root metaphor serves to direct research along a particular path in ways that often lead to a siloing of research knowledge. However, while laying bare the foundations of each metatheory and discussing the nature of the empirical projects by which they are supported, we also seek to draw them more closely together. In particular, we do this by elaborating an integrative social interactionist model in which organizational identity is understood to be the product of recursive interaction between bottom‐up and top‐down processes of identity consensualization and contestation.